Inisiasi Fixed Ratio Combination (FRC) Insulin Glargine/Lixisenatide untuk Orang Dewasa dengan Diabetes Melitus Tipe 2 - Mokoagow, Muhammad Ikhsan (PT Kalbe Farma Tbk., 2023)
Hyperglycaemia is a medical condition of increased blood glucose levels, which is characteristic of several diseases, especially diabetes mellitus. Diabetes mellitus is currently a global threat to health. A fixed-ratio combination a insulin glargine and lixisenatide (iGlarLixi) is a productcontaining glargine insulin (a long-acting insulin) and lixisenatide (a glucagon-like peptide-1 receptor agonist) in one single injection. Fixed ratio combination offers many clinical benefits for adults with type 2 diabetes mellitus.